Sistem Inventori Kontrol Material Dan Peralatan Penunjang Praktek Mahasiswa (Studi Kasus Di Work Shop Jurusan Teknik Mesin Politeknik Negeri Jakarta) - Hamdi Hamdi (Politeknik Negeri Jakarta, 2012)
Abstract Inventory Control is a mechanism for recording and reporting of inventory items. Nowaday the company / government agencies to apply the principles of the involvement of a number of applications and information technology that enables integration of all local procurement of goods and services into a process more efficient, effective, open and competitive, transparent, equitable, non-discriminatory and accountable. Long-term goals and targets of this research is to build an electronic inventory system of goods (inventory control) that can be applied at the Polytechnic. Thus the realization of a system of recording goods in the polytechnic process on line. Inventory system is built using the Zachman Framework and methodology to facilitate the encoding using object-oriented methods with UML (Unified Modeling Language) as the language in models design. Inventory system begins with the identification of system needs. Based on these needs will be the system design, which is modeled using UML. The results of this thesis in the form of an inventory system design Internet-based procurement has facilities to manage storage and recording of goods that are expected to occur no clerical error recording. Keywords: Inventories, warehouses, online Abstrak Inventori kontrol adalah mekanisme pencatatan dan pelaporan barang persediaan. Jaman sekarang ini lembaga perusahaan / pemerintah untuk menerapkan prinsip-prinsip keterlibatan sejumlah aplikasi dan teknologi informasi yang memungkinkan integrasi semua pengadaan barang dan jasa menjadi proses yang lebih efisien, efektif, terbuka dan bersaing, transparan, adil, non-diskriminatif dan akuntabel. Tujuan jangka panjang dan target dari penelitian ini adalah untuk membangun sebuah sistem elektronik persediaan barang (inventory control) yang dapat diterapkan di Politeknik. Dengan demikian realisasi sistem pencatatan barang di politeknik diproses secara on line. Sistem persediaan dibangun menggunakan Framework Zachman dan metodologi untuk memfasilitasi encoding menggunakan metode berorientasi objek dengan UML (Unified Modeling Language) sebagai bahasa dalam perancangan model. Sistem inventori dimulai dengan identifikasi kebutuhan sistem. Berdasarkan kebutuhan akan desain sistem, yang dimodelkan dengan menggunakan UML. Hasil dari tesis ini dalam bentuk inventarisasi sistem pengadaan desain berbasis Internet memiliki fasilitas untuk mengelola penyimpanan dan pencatatan barang yang diharapkan terjadi ada rekaman kesalahan administrasi. Kata kunci : Inventaris, gudang, online